2008
DOI: 10.1111/j.1442-200x.2007.02511.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of myocardial involvement using cardiac troponin‐I and echocardiography in rheumatic carditis in İzmir, Turkey

Abstract: The present results indicate the absence of myocardial involvement in acute rheumatic carditis without congestive heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
3
2
0
Order By: Relevance
“…Our results are in agreement with Tavli et al .,[13] who showed that the level of cTnI is not elevated in acute rheumatic fever in children with and without carditis. In addition, they failed to show any echocardiographic signs of myocardial involvement in their study on rheumatic fever in children.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in agreement with Tavli et al .,[13] who showed that the level of cTnI is not elevated in acute rheumatic fever in children with and without carditis. In addition, they failed to show any echocardiographic signs of myocardial involvement in their study on rheumatic fever in children.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with Gupta et al [33], Oran et al [34], Tavli et al [26] and Cunningham [35], insignificant difference was found in cTnI levels between ARF children with arthritis and with carditis as compared to healthy controls. However, the absence of elevated cTnI throughout the course of ARF in particular during active carditis may be related to insignificant cardiomyocyte injury as reported by Oran et al [34], Gupta et al [33], Williams et al [36] and Kamblock et al [37].…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the values of ASOT, ESR and CRP, insignificant differences between the three subgroups of ARF were in agreement with Alehan et al [23]; El Amrousy et al [24]; Roodpeyma et al [25] and Tavli et al [26]. Their prospective studies were performed on patients with acute rheumatic valvular disease using echocardiography and cTnI in order to detect myocardial involvement.…”
Section: Discussionsupporting
confidence: 81%
“…Hence, many countries have proposed their own echocardiographic parameters in order not to underdiagnose subclinical or latent silent carditis. [6][7][8] However, there are no available data regarding left ventricular (LV) dyssynchrony in children with ARF.…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatic carditis may be mild and can evolve over weeks to months and may course without clinical manifestation. Hence, many countries have proposed their own echocardiographic parameters in order not to underdiagnose subclinical or latent silent carditis . However, there are no available data regarding left ventricular (LV) dyssynchrony in children with ARF.…”
Section: Introductionmentioning
confidence: 99%